First Nations' Food Self-Determination Activities - Nishawbe Aski Nation (2021)
This infographic was prepared by Nishawbe Aski Nation with the support of the Northern Food Systems Community Project Coordinator in partnership with Eko Nomos and the Community Engaged Scholarship Institute. It explores a spectrum of First Nations' food self-determination activities, including traditional practices, nutrition practices, imported food, and local production.